Analysis of the Influence of Strategic Human Resource Management and Rule Breaking Moderated by Servant Leadership On Job Satisfaction and Work Engagement On Adaptive Performance at PT. XYZ in Tangerang - Qonita, Widya; Yohana F. Cahya Palupi Meilani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the influence of Strategic Human Resource Management (SHRM), servant leadership, job satisfaction, work engagement, and rule breaking on adaptive performance among millennial-generation production employees at PT XYZ. The research method used was a quantitative approach with a cross-sectional design, involving 85 respondents through an online questionnaire and analyzed using SmartPLS 4.1.0.8. The results showed that SHRM had a positive and significant effect on job satisfaction, but no effect on rule breaking. Servant leadership had a positive effect on job satisfaction and work engagement, but no significant effect on rule breaking and did not act as a moderator between SHRM and job satisfaction or rule breaking. Work engagement and job satisfaction were shown to have a positive effect on adaptive performance, with significant mediation found only in the path from servant leadership through work engagement to adaptive performance. The conclusion of this study is that SHRM is more effective in increasing job satisfaction, while servant leadership plays an important role in building work engagement, and both indirectly support increased adaptive performance. Keywords: Strategic Human Resource Management, Servant Leadership, Job Satisfaction